The Effectiveness of Lemongrass Aromatherapy in Reducing Nausea and Vomiting in Pregnant Women - Hotimah, Ucu Husnul; Rahmadhena, Melisa Putri (Indonesian Journal of Global Health Research, 2024)
Nausea and vomiting in pregnancy is a common symptom, but worsening of the condition due to hyperemesis gravidarum can often have a significant impact on a woman's quality of life, both personally and professionally, and cause emotional trauma. Various alternative non-pharmacological treatments have been developed to maintain the safety of the mother and fetus. One of them is lemongrass or lemongrass aromatherapy. The aim of this study was to analyze the effectiveness of lemongrass aromatherapy in reducing nausea and vomiting in pregnant women in the first trimester. This research is a type of intervention research with a quasi-experimental design in the intervention group and control group without randomization. The research was conducted in the Cimarga Community Health Center area in September 2023. The sample used was 32 pregnant women collecting by purposive sampling The analysis was used Independent sample t-test.The results of the Independent sample t-test obtained p value of 0.021 < 0.05, so it can be concluded that there is an effect of giving Lemongrass Aromatherapy on reducing nausea and vomiting in first trimester pregnant women. Lemongrass aromatherapy is effective in reducing the frequency of nausea and vomiting in first trimester pregnant women.